Does Intention Matter? Relations between Parent Pointing, Infant Pointing, and Developing Language Ability. Issue 5 (20th October 2019) - Salo, Virginia C.; Reeb-Sutherland, Bethany; Frenkel, Tahl I.; Bowman, Lindsay C.; Rowe, Meredith L.
ABSTRACT: Infants' pointing is associated with concurrent and later language development. The communicative intention behind the point – i.e., imperative versus declarative – can affect both the nature and strength of these associations, and is therefore a critical factor to consider. Parents' pointing is associated with both infant pointing and infant language; however, less work has examined the intent behind parents' points. We explore relations between parents' and infants' pointing at the level of communicative intention, and examine how pointing relates to concurrent and longitudinal infant language skills. In a sample of 52 mother-infant dyads, we measured mother and infant pointing at infant age 12-months, and infant expressive and receptive language at 12-, 18-, and 24-months. We found that mothers produced points with a variety of intentions, however we did not find relations between mother and infant pointing within the different communicative intentions. Replicating previous research, infant declarative pointing was related both concurrently and longitudinally to their language ability. Mothers' declarative pointing was related to their infants' concurrent language, while their imperative pointing was not. Further, there was an interaction between parent and infant declarative pointing, such that the positive relation between parents' declarative pointing and their infants' concurrent receptive language was present only for those infants who were also producing declarative points themselves. Findings suggest that parents' declarative pointing may support both their infants' early word learning and, perhaps, provides a model for their infant to begin using points as well. This study constitutes an important initial exploration of these relations.